A NEW NATURAL HYBRID OF NEPENTHES FROM MT. KINABALU ( SABAH ) - Jummat H. Adam; C.C Wilcock (Reinwardtia, 1992)
A new natural hybrid of Nepenthes, N. x alisaputraiana, from Mt. Kina- balu Sabah is described.